YALÇIN, SÜLEYMAN KAAN (2018). A GRAMMAR OF AZERBAIJAN TURKISH, KESİT PUBLICATIONS, ISBN 978-6059408-94-3, 448 PAGES - Murat Aka (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2019)
Many studies is conducted about Azerbaijan Turkish in Turkey and outside of Turkey. One of the recent studies about Azerbaijan Turkish was carried out by Assoc. Dr. Süleyman Kaan Yalçın. His study was published as a Grammar of Azerbaijan Turkish in 2018. The study has dealt with phonetics and morphology of Azerbaijani Turkish in much more detailed way compared to previous studies. Historical and modern comparisons are also made occasionally in the book. In generally, The study is detailed grammar (phonetics and morphology) about written language of Republic of Azerbaijan. In other words, It includes grammar of Northern Azerbaijan Turkish. In this paper, the book called a Grammar of Azerbaijan Turkish will be introduced.